2020
DOI: 10.21608/edj.2020.26079.1076
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparative evaluation of different retraction systems in gingival displacement and their influence on periodontal health: A randomized clinical trial

Abstract: Purpose: This randomized clinical study was to assess cordless techniques compared to conventional cords in gingival displacement and effect on periodontal health. Material and Methods:Forty participants having a premolar abutment were elected following inclusion criteria and allocated by using parallel randomization into four groups (n=10) for gingival retraction either with Ultrapak, GingiTrac, Traxodent or NoCord. By single-blinded operator, the horizontal gingival displacement as a primary outcome was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…The values obtained for the cotton-based retraction cord (Ultrapak) agree with values obtained in previous studies by Al Hamad et al [ 12 ], Madaan et al [ 17 ], Chaudhari et al [ 20 ], and Gajbhiye et al [ 22 ]. Our results also are in agreement with the results obtained between the 2 investigated materials after retraction [ 12 , 17 , 20 , 22 , 39 ]. While differences of mean values are attributed to different methods and techniques (mid-section versus 4 or 6 surfaces on the tooth) of sulcus width evaluation, the outcome of the result remains same.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The values obtained for the cotton-based retraction cord (Ultrapak) agree with values obtained in previous studies by Al Hamad et al [ 12 ], Madaan et al [ 17 ], Chaudhari et al [ 20 ], and Gajbhiye et al [ 22 ]. Our results also are in agreement with the results obtained between the 2 investigated materials after retraction [ 12 , 17 , 20 , 22 , 39 ]. While differences of mean values are attributed to different methods and techniques (mid-section versus 4 or 6 surfaces on the tooth) of sulcus width evaluation, the outcome of the result remains same.…”
Section: Discussionsupporting
confidence: 92%
“…Our results also show that polymer-based cord took less time for placement (Gp C 157.1 versus Gp P 140.3). Our results for Ultrapak retraction cord (cotton) show similar placement time values as in earlier [6,12,17] and recent [39] studies.…”
Section: Clinical Parameterssupporting
confidence: 90%
“…Egypt, 20 Indonesia 24 and Iran. 13 Twelve studies 2,10,12-14,20-23,26-28 reported the teeth treated in the studies (incisors, canines, premolars and molars).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…the exception of Gupta et al,11 and Sachdev et al,28 who used dry cords and those of Beleidy et al,20 and Jain et al,12 who Effectiveness of cordless techniques in gingival displa-cement. A systematic review and meta-analysis.…”
mentioning
confidence: 99%
“…Clinicians typically describe a lengthy placement process, as well as pain, bleeding, and induction of an acute gingival injury. Additionally, packing the cord into the sulcus may result in biological width violation and junctional epithelium injury, which can cause gingival recession, bone resorption, and even infection (Beleidy and Serag Elddien, 2020). Both methods are technique-sensitive, costly, and timeconsuming.…”
Section: Introductionmentioning
confidence: 99%